Hubungan Pemanfaatan Internet dalam Pembelajaran dengan Hasil Belajar Siswa - Yelmi Yunarti (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2017)
The purpose of this study was to determine a significant positive relationship between internet utilization and student learning outcomes in SMA Negeri 1 OKU. This research is quantitative research using correlation method. The sample in this research is 216 students. Data collection in this research is using questionnaire. Data analysis using Pearson Product Moment formula. Based on the results of research elements of internet utilization in learning in SMA Negeri 1 OKU get good value is in terms of internet as a medium. While the weakest is the use of e-learning for learning. The result of the value of the correlation coefficient is 0.769. The correlation coefficient of 0.569 is included in the strong category. This shows a strong relationship of variable X (the use of Internet in Learning) with variable Y (learning outcomes) in students of SMA Negeri 1 OKU.